Struktur Komunitas Mikroartropoda Bryofauna Terestrial Di Zona Tropik Gunung Ungaran, Semarang, Jawa Tengah - Munarsih, Atik; Rahadian, Rully; Hadi, Mochamad (Bioma : Berkala Ilmiah Biologi, 2014)
Bryofauna is all of the animal life which associated with moss. Actually, biodiversity of bryofauna have not been studied much in Indonesia. Research on community structure of terrestrial microarthropod bryofauna has been done in three different altitudes in the tropical zone of the Ungaran Mountain, Semarang, Central Java. The objective of this study is to compare community structure of bryofauna contained in three different altitudes in the tropical zone. The research was conducted from April to November 2012. Sampling was carried out at 3 stations with the different heights that are the station I with an altitude 750 m asl, the altitude of the station II with an altitude 980 m asl and the station III with an altitude of 1100 m asl. Sampling was done purposively using square plot method. Bryofauna identification was conducted in Ecology and Biosistematics Laboratory University of Diponegoro and Entomologi Laboratory of Zoology Departement Indonesian Institute of Sciences. The results shows that the tropical zone have5 classes, 16 orders and 31 suborders/family of bryofauna. Mesostigmata and Oribatida was the dominant taxa at all heights except at an altitude of 980 m asl, Oribatida was categorized as subdominant. Diversity of bryofauna at different heights shows that decreasing diversity patterns, along with the increasing altitude. In general, the distribution of bryofauna at different heights is quite spread evenly with the flattening index values ​​betweens 0.84 to 0.94. Bryofauna taxsa richness and diversity of bryophytes at different heights in the tropical zone showed the same pattern fluctuated. Taxa group which play a role as predator are taxa that the most abundant in the tropical zone of the Ungaran Mount. Keywords:Bryofauna terrestrial, bryophytes, Ungaran mount, community structure